2023
DOI: 10.4322/bds.2023.e3854
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the efficacy of Etoricoxib in reducing post-operative pain associated with minor oral surgery. A randomized clinical trial

Yusra Hameed AL-MUKHTAR,
Zaid Hazim DELEME,
Ahmed Salih KHUDHUR

Abstract: Etoricoxib, a new cyclooxygenase-2-selective inhibitor has demonstrated a rapid onset analgesic effect for relieving acute pain especially when prescribed as a pre-emptive medication. On these bases, this study may provide useful information and guidance for clinicians working in the field of oral surgery, as regards handling odontogenic pain and postoperative pain precisely with cyclooxygenase-2 inhibitors. Objective: the study aimed to measure the quantifiable efficacy of Etoricoxib in reducing post-extracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The study showed no statistically significant difference in either group after patients were administered drugs 30 minutes before the procedure. The study suggested that etoricoxib can be used as a preemptive medication to reduce pain [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The study showed no statistically significant difference in either group after patients were administered drugs 30 minutes before the procedure. The study suggested that etoricoxib can be used as a preemptive medication to reduce pain [ 14 ].…”
Section: Introductionmentioning
confidence: 99%